Proposed Marketing Strategy Emphasize on Competitor Analysis on Sentra Timur Residence - Junaidin, Sefta Marisa Dwipasari; Wibowo, Satya Aditya (The Indonesian Journal of Business Administration, 2014)
Abstract – Enhancement of economic level has put Indonesia into one of many investment destination. Population growth which accompanied by the increasing number of immigrants who work in the Jakarta and the increasing number of upper-middle class, has made the need to have a place to stay in Jakarta increasing. The fact that needs for housing not accompanied with the increase of land, make vertical housing such as apartments more attractive. In this regard, the thesis will be discussed one of the existing vertical housing in East Jakarta, namely Sentra Timur Residence (STR). The discussion will be focused on the marketing strategy of STR in the face of an increasing number of competitors. Therefore, to analyze whether competitor factor influence significantly to STR sales volume or not we use some analysis which are: PEST, Porter’s 5 Forces, SWOT analysis, and customer analysis. Based on the analysis, it can be concluded that at this time competitors do not have a significant effect on the  sales of STR. The fundamental problem that cause slow growth in sales is due to the following matters: 1) Lack of control to the project contractor that gave impact (delay) on the target of unit handover. 2) Unattractive promotion campaign. 3) Many customers stated does not get the message about green eco-building concept to be conveyed by STR. 4) There is no effective management review of the marketing strategies that have been done, and there is no management review regarding the STR service to customers. Keywords: marketing strategy, apartment.